Characterization of the external female genitalia of six species of Triatominae (Hemiptera: Reduviidade) by scanning electron microscopy - da Rosa, João Aristeu [UNESP]; Mendonça, Vagner José; Rocha, Cláudia Solano [UNESP]; Gardim, Sueli [UNESP]; Cilense, Mario [UNESP] (FapUNIFESP (SciELO), 2010)
By macroscopic and microscopic dorsal side observation, it was noted that the IX and X segments of two species each of Panstrongylus and Triatoma terminate in an elongated way, whereas they terminate abruptly in the two species of Rhodnius. Scanning observation of the dorsal, ventral, lateral and posterior sides of the female genitalia of Panstrongylus herreri, Panstrongylus megistus, Rhodnius colombiensis, Rhodnius prolixus, Triatoma infestans and Triatoma vitticeps revealed that these six species are generally and specifically distinguished based on these elements. We describe several components that distinguish P. herreri from P. megistus: four on the dorsal side: the VII, VIII, IX and X segments, on the ventral view, three: VII sternite, VIII gonocoxite and VIII gonapophyse, on the lateral view one character, VIII gonocoxite and on the posterior view three characters: VIII and IX gonocoxite and XI gonopophyse. Comparing R. colombiensis and R. prolixus, there were three distinct characters on the dorsal side: the VII, VIII and X segments, on the ventral view three characters: the IX and X segments and VIII gonocoxite and on the posterior view four characters: the VIII, IX, X segments and VIII gonapophyse that distinguish the two species. T. infestans and T. vitticeps have four different characters on the dorsal side: the VII, VIII, IX and X segments, on the ventral view four characters: the VII and X segments, VIII gonocoxite and VIII gonapophyse, on the lateral view two characters, IX and X segments and on the posterior view four characters: the IX and X segments, VIII gonocoxite and VIII gonapophyse that distinguish the two species. Examination of the external female genitalia of six triatomine species by scanning suggests that these components are useful for taxonomical studies.
Keywords: External female genitalia; Taxonomy; Triatominae